P5 6 The SpinLaunch Orbital Accelerator - Munt, Leon; Sanjeevvijay, Shaswathan; Iordanidis, George (Physics Special Topics, 2024)
This paper presents the calculations and analysis of the proposed SpinLaunch orbital accelerator. Despite successful test launches with the sub-orbital accelerator, critics have questioned the feasibility of the full scale orbital accelerator. The analysis in this paper determines the carbon fibre tether used in the accelerator is capable of what is required